Corporate social responsibility (CSR) implementation a review and a research agenda towards an integrative framework - Fatima, Tahniyath; Elbanna, Said (2023)
In spite of accruing concerted scholarly and managerial interest since the 1950s in corporate social responsibility (CSR), its implementation is still a growing topic as most of it remains academically unexplored. As CSR continues to establish a stronger foothold in organizational strategies, understanding its implementation is needed for both academia and industry. In an attempt to respond to this need, we carry out a systematic review of 122 empirical studies on CSR implementation to provide a status quo of the literature and inform future scholars. We develop a research agenda in the form of an integrated framework of CSR implementation that pronounces its multi-dimensional and multi-level nature and provides a snapshot of the current literature status of CSR implementation. Future research avenues relating to multi-level studies, theoretically supported research models, developing economy settings, and more are recommended. Practitioners can also benefit through utilizing the holistic framework to attain a bird’s eye view and proactively formulate and implement CSR strategies that can be facilitated by collaborations with CSR scholars and experts.
Keywords: CSR complexity; CSR formulation; CSR implementation framework; CSR strategy; Corporate social responsibility implementation; Aufsatz in Zeitschrift